Time-motion, heart rate, perceptual and motor behaviour demands in small-sides soccer games: Effects of pitch size - Casamichana, D.; Castellano, J. (Journal of Sports Sciences, 2010)
The aim of this study was to examine physical, physiological, and motor responses and perceived exertion during different soccer drills. In small-sided games, the individual playing area (~275 m2, ~175 m2, and ~75 m2) was varied while the number of players per team was kept constant: 5 vs. 5 plus goalkeepers. Participants were ten male youth soccer players. Each session comprised three small-sided game formats, which lasted 8 min each with a 5-min passive rest period between them. A range of variables was recorded and analysed for the three drills performed over three training sessions: (a) physiological, measured using Polar Team devices; (b) physical, using GPS SPI elite devices; (c) perceived exertion, rated using the CR-10 scale; and (d) motor response, evaluated using an observational tool that was specially designed for this study. Significant differences were observed for most of the variables studied. When the individual playing area was larger, the effective playing time, the physical (total distance covered; distances covered in low-intensity running, medium-intensity running, and high-intensity running; distance covered per minute; maximum speed; work-to-rest ratio; sprint frequency) and physiological workload (percent maximum heart rate; percent mean heart rate; time spent above 90% maximum heart rate), and the rating of perceived exertion were all higher, while certain motor behaviours were observed less frequently (interception, control and dribble, control and shoot, clearance, and putting the ball in play). The results show that the size of the pitch should be taken into account when planning training drills, as it influences the intensity of the task and the motor response of players.